Carbon fiber hard felt surface anti-oxidation coating and preparation method thereof

By curing the carbon fiber hard felt three times and graphitizing the high-temperature carbon fiber hard felt, a carbon fiber hard felt with excellent oxidation coating was prepared, which solved the problem of the material being easily corroded in a high-temperature environment, extended the service life and reduced production costs.

CN119531135APending Publication Date: 2025-02-28HUZHOU HUANKEN ZHONGXIN NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411579214.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing carbon fiber hard felt materials are susceptible to physical erosion and chemical corrosion in high temperature environments, resulting in reduced insulation performance and shortened service life.

Method used

Carbon fiber hard felt with excellent antioxidant coating was prepared by curing the carbon fiber hard felt matrix three times, including one high temperature graphitization. Specific steps include coating and curing using different formulas of coating glue to form a tight crosslinking network structure to improve the wear resistance and oxidation resistance of the coating.

Benefits of technology

It achieves efficient curing and improved oxidation resistance of carbon fiber hard felt surface coating, extends the service life of the material, and reduces production costs and cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005122590490000011
    Figure HDA0005122590490000011
Patent Text Reader

Abstract

The invention discloses a carbon fiber hard felt surface anti-oxidation coating and a preparation method thereof, and the carbon fiber hard felt with an excellent anti-oxidation coating on the surface is prepared by performing three times of coating curing and one time of high-temperature graphitization on a carbon fiber hard felt matrix. Compared with the prior art, the high thermal insulation performance and the excellent surface coating performance of the hard carbon fiber thermal insulation felt are guaranteed, meanwhile, the use frequency of a high-energy-consumption equipment graphitization furnace is reduced, the coating efficiency and the surface coating performance are improved, the whole product period is shortened, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature thermal field carbon fiber thermal insulation composite materials, and in particular to an anti-oxidation coating on the surface of a carbon fiber hard felt and a preparation method thereof. Background Art

[0002] As a new type of high-temperature thermal insulation material, carbon fiber composite material hard felt has the excellent characteristics of low density, low thermal conductivity, chemical corrosion resistance, easy molding, low impurity content and high temperature stability. It is widely used in photovoltaics, semiconductors, high-end metallurgical heat treatment, sapphire, aerospace and other industries that require harsh high-temperature environments. With the rapid development of the third-generation semiconductors, solar photovoltaic industry, and optical fiber industry, the market demand for semiconductors such as single crystal silicon, polycrystalline silicon, SiC, and GaN has increased sharply. Carbon fiber hard felt materials are essential advanced thermal insulation materials in high-temperature industrial equipment (single crystal silicon furnaces, polycrystalline silicon furnaces, optical fiber drawing furnaces, semiconductor crystal growth furnaces), and there are higher requirements for their demand, high temperature resistance and service life.

[0003] At present, most high-temperature furnace equipment uses inert gas for cooling during operation. The particulate impurities in the furnace form a high-speed particle flow under the action of the airflow, which physically scours the surface of the carbon fiber felt. The silicon vapor in the production process will react with the carbon fiber at a high temperature of 1500°C, further corroding the carbon fiber felt, causing the carbon fiber felt to be physically and chemically damaged, causing the insulation material to age and become thinner, and its life span is seriously shortened. The current technical solution is to form an anti-oxidation and anti-corrosion protective layer on the surface of the carbon fiber. The conventional method is to attach a layer of graphite paper to the carbon fiber felt during the molding process, or to form a silicon carbide or pyrolytic carbon coating on the surface by chemical deposition or other means after the carbon fiber felt is formed, or to manually apply two layers of graphite powder coating on the surface of the felt.

[0004] Due to the inconsistency in the thermal expansion coefficients of graphite paper and carbon fiber felt, during use, after high-temperature and low-temperature cycles, the interfacial bonding force between graphite paper and carbon fiber felt gradually weakens, and graphite paper is easily peeled off under air flow. Foreign matter generated during the graphite paper shedding process affects crystal growth, and the thermal insulation performance and life of the carbon fiber felt are seriously affected. It is only suitable for simple flat or cylindrical products. It is difficult to lay graphite paper on products with complex shapes or hollow parts in the middle. Summary of the invention

[0005] The present invention prepares a carbon fiber hard felt with an excellent anti-oxidation coating on the surface by three times of coating curing and one time of high-temperature graphitization on the carbon fiber hard felt substrate. Compared with the existing technology, while ensuring the high thermal insulation performance and excellent surface coating performance of the hard carbon fiber insulation felt, the number of times the graphitization furnace of high energy consumption equipment is used is reduced, the coating efficiency and surface coating performance are improved, the entire product cycle is shortened, and the production cost is reduced.

[0006] The purpose of the present invention is to provide an anti-oxidation coating on the surface of a carbon fiber hard felt insulation material and a preparation method thereof based on existing research, so as to improve the life of the insulation felt and reduce the cost and production cycle while ensuring the good thermal insulation performance of the hard felt material.

[0007] To solve the above problems, the technical solution of the present invention is:

[0008] A carbon fiber hard felt surface anti-oxidation coating is prepared by subjecting a carbon fiber hard felt substrate to three coating curing steps and one high-temperature graphitization step to obtain the carbon fiber hard felt surface anti-oxidation coating. During the three coating curing steps, the coating glue used for the first time is: 25-28 parts of anhydrous ethanol, 1-3 parts of resin, and 0.2-0.5 parts of carbon powder; the coating glue used for the second time is: 25-30 parts of graphite emulsion, 8-10 parts of flake graphite powder, 2-5 parts of silicon carbide powder, and 10-12 parts of water; and the coating glue used for the third time is: 10-12 parts of anhydrous ethanol, 1-3 parts of resin, and 0.1-0.3 parts of graphite powder.

[0009] A method for preparing an anti-oxidation coating on the surface of a carbon fiber hard felt, the preparation method comprising the following steps:

[0010] S1. Surface treatment Ⅰ

[0011] Use coarse sandpaper to polish the carbon fiber hard felt substrate and blow away the dust on the surface of the substrate;

[0012] S2, applying the first coating glue solution. The first coating glue solution is: 25-28 parts of anhydrous ethanol, 1-3 parts of resin I, and 0.2-0.5 parts of carbon powder;

[0013] S3, curing, drying and curing, the heating rate does not exceed 10℃ / min, the curing temperature is 180-220℃, and the curing time is 60-90min;

[0014] S4. Surface treatment II. Applying the second coating glue

[0015] After grinding and blowing, apply the second coating glue, the second coating glue is: 25-30 parts of graphite emulsion, 8-10 parts of flake graphite powder, 2-5 parts of silicon carbide powder, 10-12 parts of water;

[0016] S5. Baking

[0017] The baking temperature is 100-120°C and the baking time is 30-90 minutes;

[0018] S6. Surface treatment III: Apply the third coating glue

[0019] After grinding and purging, apply the third coating glue, which is: 10-12 parts of anhydrous ethanol, 1-3 parts of resin II, and 0.1-0.3 parts of graphite powder;

[0020] S7, curing and sintering

[0021] The curing temperature is 180-200°C, the curing time is 30-60 minutes, the sintering temperature is 1700°C-2200°C, and the sintering time is 4-6 hours. In step S2, the resin I is a mixed solution of phenolic resin and furan resin, and the mass ratio thereof is 1:0.5-0.8.

[0022] The carbon powder particle size is 30-50 μm.

[0023] In step S6, the resin II is a phenolic resin.

[0024] In step S6, the graphite powder has a particle size of 80-100 μm.

[0025] In step S1, the coarse sandpaper used for grinding is 400-600 mesh.

[0026] In step S4, the coarse sandpaper used for grinding is 120 mesh, 320 mesh and 600 mesh.

[0027] In step S6, the coarse sandpaper used for grinding is 800 grit.

[0028] Beneficial Effects of the Invention

[0029] The key point of the present invention is to use three groups of coating glues with different formulations. The first coating glue forms a bottom protective layer with excellent bonding force on the surface of the carbon fiber hard felt matrix. The carbon powder in the first glue fills the fiber holes on the matrix surface. The cross-linked structure formed after the phenolic resin and furan resin are cured ensures that the surface protective coating and the hard carbon fiber matrix material form a good interface bonding force, so that the coating is not easy to fall off and be damaged. The glue formed by its preferred ratio makes the bottom protective layer have moderate hardness and is not easy to fall off and crack. The graphite emulsion, silicon carbide powder and graphite flake powder in the second coating glue make the surface of the carbon fiber hard felt have a coating with better oxidation resistance, the surface roughness and hardness of the hard felt are greatly improved, and its wear resistance, physical impact resistance and oxidation resistance and corrosion resistance are greatly improved. On the basis of the first two glue coatings, the third coating glue concentration is higher, the formed cross-linked network structure is tighter, the surface coating after carbonization and graphitization has more cross-linking points, and the coating is not easy to crack, so that the carbon fiber hard felt has a longer service life.

[0030] The anti-oxidation coating on the surface of the hard carbon fiber thermal insulation felt prepared by the technical solution mentioned in the present invention is well bonded with the substrate interface, the surface coating is not easy to fall off, the anti-oxidation performance and wear resistance are enhanced, and the carbon fiber thermal insulation felt has a longer service life;

[0031] The preparation process of the anti-oxidation coating on the surface of the carbon fiber hard felt mentioned in the present invention has a short manufacturing cycle, avoids repeated use of a high-energy-consuming graphitization furnace, has low production cost, strong operability, and can meet the needs of large-scale low-cost industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The figure is a flow chart showing a method for preparing an anti-oxidation coating on the surface of carbon fiber hard felt. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be further described below through specific embodiments.

[0034] Example 1

[0035] A method for preparing an anti-oxidation coating on the surface of a carbon fiber hard felt thermal insulation material, specifically comprising the following steps:

[0036] Prepare a carbon fiber hard felt substrate, polish it with 600-grit coarse sandpaper, and then use an air gun to blow away the carbon fiber dust on the surface of the substrate;

[0037] A primary coating glue solution is prepared, including the following raw materials in parts by weight: 25 parts of anhydrous ethanol, 1 part of resin (a mixed solution of phenolic resin and furan resin, with a mass ratio of 1:0.5), and 0.3 parts of carbon powder with a particle size of 50 μm;

[0038] Use a mixer to mix the primary coating liquid evenly, and use a wool brush to evenly apply the glue liquid on the surface of the carbon fiber substrate from the inside out to ensure that the carbon fiber hard felt substrate has no exposed bottom, no pits, no protrusions and other defects;

[0039] The carbon fiber hard felt substrate after a layer of coating is placed in an oven for drying and curing, with a heating rate of 10°C / min, a curing temperature of 200°C, and a curing time of 45min;

[0040] Use 120-mesh, 320-mesh and 600-mesh coarse sandpaper to grind the carbon fiber substrate until the surface is smooth and there is no granularity on the substrate surface. Use an air gun to blow away the dust on the substrate surface.

[0041] Prepare a secondary coating glue solution, including the following raw materials in parts by weight: 30 parts of graphite emulsion, 8 parts of flake graphite powder, 2 parts of silicon carbide powder, and 12 parts of pure water;

[0042] Apply the evenly stirred secondary coating liquid to the surface of the carbon fiber hard felt substrate;

[0043] The carbon fiber hard felt substrate after the secondary coating was placed in an oven for baking at a temperature of 120°C for 60 minutes.

[0044] Use 800-grit coarse sandpaper to polish the dried secondary coating hard felt substrate, and use an air gun to blow out the dust particles on the substrate surface;

[0045] The third coating glue solution is prepared, including the following raw materials in parts by weight: 10 parts of anhydrous ethanol, 1 part of phenolic resin, and 0.2 parts of graphite powder (particle size is 100 μm);

[0046] Apply the three-layer glue evenly on the surface of the hard felt substrate without leaking the bottom and without producing pits and protrusions;

[0047] The carbon fiber after three coatings should be placed in an oven on the substrate for curing at a temperature of 180°C and a curing time of 45 minutes;

[0048] The cured carbon fiber hard felt matrix is ​​placed in a low-temperature purification furnace for sintering. The entire sintering process is in an inert gas environment. The sintering temperature is 1700°C and the sintering time is 4-6 hours to obtain a hard carbon fiber insulation felt with an excellent anti-oxidation protective layer on the surface.

[0049] The density, thermal insulation performance, roughness, hardness and thermal weight loss of the coated carbon fiber felt were tested.

[0050] Example 2

[0051] A preparation process of an anti-oxidation coating on the surface of a carbon fiber hard felt thermal insulation material, specifically comprising the following steps:

[0052] Prepare a carbon fiber hard felt substrate, polish it with 600-grit coarse sandpaper, and then use an air gun to blow away the carbon fiber dust on the surface of the substrate;

[0053] A primary coating glue solution is prepared, including the following raw materials in parts by weight: 28 parts of anhydrous ethanol, 1.5 parts of resin (a mixed solution of phenolic resin and furan resin, with a ratio of 1:0.5), and 0.5 parts of carbon powder with a particle size of 50 μm;

[0054] Use a mixer to mix the primary coating liquid evenly, and use a wool brush to evenly apply the glue liquid on the surface of the carbon fiber substrate from the inside out to ensure that the carbon fiber hard felt substrate has no exposed bottom, no pits, no protrusions and other defects;

[0055] The carbon fiber hard felt substrate after a layer of coating is placed in an oven for drying and curing, with a heating rate of 10°C / min, a curing temperature of 200°C, and a curing time of 60min;

[0056] Use 120-mesh, 320-mesh and 600-mesh coarse sandpaper to grind the carbon fiber substrate until the surface is smooth and there is no granularity on the substrate surface. Use an air gun to blow away the dust on the substrate surface.

[0057] Prepare a secondary coating glue solution, including the following raw materials in parts by weight: 25 parts of graphite emulsion, 10 parts of flake graphite powder, 2 parts of silicon carbide powder, and 10 parts of pure water;

[0058] Apply the evenly stirred secondary coating liquid to the surface of the carbon fiber hard felt substrate;

[0059] The carbon fiber hard felt substrate after the secondary coating was placed in an oven for baking at a temperature of 120°C for 60 minutes.

[0060] Use 800-grit coarse sandpaper to polish the dried secondary coating hard felt substrate, and use an air gun to blow out the dust particles on the substrate surface;

[0061] The third coating glue solution is prepared, including the following raw materials in parts by weight: 10 parts of anhydrous ethanol, 1.5 parts of phenolic resin, and 0.5 parts of graphite powder (particle size is 100 μm);

[0062] Apply the three-layer glue evenly on the surface of the hard felt substrate without leaking the bottom and without producing pits and protrusions;

[0063] The carbon fiber after three coatings should be placed in an oven on the substrate for curing at a temperature of 180°C and a curing time of 60 minutes;

[0064] The cured carbon fiber hard felt matrix is ​​placed in a low-temperature purification furnace for sintering. The entire sintering process is in an inert gas environment. The sintering temperature is 1850°C and the sintering time is 6 hours to obtain a hard carbon fiber insulation felt with an excellent anti-oxidation protective layer on the surface.

[0065] The density, thermal insulation performance, roughness, hardness and thermal weight loss of the coated carbon fiber felt were tested.

[0066] Example 3

[0067] A preparation process of an anti-oxidation coating on the surface of a carbon fiber hard felt thermal insulation material, specifically comprising the following steps:

[0068] Prepare a carbon fiber hard felt substrate, polish it with 600-grit coarse sandpaper, and then use an air gun to blow away the carbon fiber dust on the surface of the substrate;

[0069] A primary coating glue solution is prepared, including the following raw materials in parts by weight: 26 parts of anhydrous ethanol, 3 parts of resin (a mixed solution of phenolic resin and furan resin, with a ratio of 1:0.5), and 0.5 parts of carbon powder with a particle size of 50 μm;

[0070] Use a mixer to mix the primary coating liquid evenly, and use a wool brush to evenly apply the glue liquid on the surface of the carbon fiber substrate from the inside out to ensure that the carbon fiber hard felt substrate has no exposed bottom, no pits, no protrusions and other defects;

[0071] The carbon fiber hard felt substrate after a layer of coating was placed in an oven for drying and curing, with a heating rate of 10°C / min, a curing temperature of 220°C, and a curing time of 45min;

[0072] Use 120-mesh, 320-mesh and 600-mesh coarse sandpaper to grind the carbon fiber substrate until the surface is smooth and there is no granularity on the substrate surface. Use an air gun to blow away the dust on the substrate surface.

[0073] Prepare a secondary coating glue solution, including the following raw materials in parts by weight: 30 parts of graphite emulsion, 8 parts of flake graphite powder, 5 parts of silicon carbide powder, and 12 parts of pure water;

[0074] Apply the evenly stirred secondary coating liquid to the surface of the carbon fiber hard felt substrate;

[0075] The carbon fiber hard felt substrate after the secondary coating was placed in an oven for baking at a temperature of 120°C for 60 minutes.

[0076] Use 800-grit coarse sandpaper to polish the dried secondary coating hard felt substrate, and use an air gun to blow out the dust particles on the substrate surface;

[0077] The third coating glue solution is prepared, including the following raw materials in parts by weight: 12 parts of anhydrous ethanol, 1.5 parts of phenolic resin, and 0.5 parts of graphite powder (particle size is 100 μm);

[0078] Apply the three-layer glue evenly on the surface of the hard felt substrate without leaking the bottom and without producing pits and protrusions;

[0079] The carbon fiber after three coatings should be placed in an oven on the substrate for curing at a temperature of 180°C and a curing time of 90 minutes;

[0080] The cured carbon fiber hard felt matrix is ​​placed in a low-temperature purification furnace for sintering. The entire sintering process is in an inert gas environment. The sintering temperature is 1850°C and the sintering time is 4 hours to obtain a hard carbon fiber insulation felt with an excellent antioxidant protective layer on the surface.

[0081] The density, thermal insulation performance, roughness, hardness and thermal weight loss of the coated carbon fiber felt were tested.

[0082] Thermal gravimetric test: A 100g test sample is placed in the test chamber of a thermal gravimetric test furnace to simulate the actual operating conditions of a high-temperature furnace. Inert gas argon is introduced as a protective gas throughout the entire process. The temperature is increased at a rate of 8-10℃ / min below 1000℃, and the temperature increase rate from 1000℃ to 1600℃ is controlled at 5℃ / min. After heating to 1600℃, the sample is kept warm for 30 minutes. The test result is the weight loss of the sample after 30 minutes of insulation. The greater the loss, the worse the antioxidant performance of the sample.

[0083] The following table shows the test results of uncoated carbon fiber hard felt and implementation cases 1-3. It can be seen from the following test results that the thermal insulation performance of the anti-oxidation coated hard felt prepared by the present invention is basically consistent with that of the bare felt, the density, roughness and hardness are improved, and the thermal weight loss is seriously reduced.

[0084]

[0085] Table 1

Claims

1. An anti-oxidation coating on the surface of a carbon fiber hard felt, characterized in that: The carbon fiber hard felt substrate is subjected to three coating curing steps and one high-temperature graphitization step to prepare an anti-oxidation coating on the surface of the carbon fiber hard felt. During the three coating curing steps, the coating adhesive used for the first time is: 25-28 parts of anhydrous ethanol, 1-3 parts of resin, and 0.2-0.5 parts of carbon powder; the coating adhesive used for the second time is: 25-30 parts of graphite emulsion, 8-10 parts of flake graphite powder, 2-5 parts of silicon carbide powder, and 10-12 parts of water; the coating adhesive used for the third time is: 10-12 parts of anhydrous ethanol, 1-3 parts of resin, and 0.1-0.3 parts of graphite powder.

2. The method for preparing the anti-oxidation coating on the surface of carbon fiber hard felt according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Surface treatment Ⅰ Use coarse sandpaper to polish the carbon fiber hard felt substrate and blow away the dust on the surface of the substrate; S2, apply the first coating glue Apply the first coating glue, the first coating glue is: 25-28 parts of anhydrous ethanol, 1-3 parts of resin I, 0.2-0.5 parts of carbon powder; S3, solidification Drying and curing, the heating rate shall not exceed 10℃ / min, the curing temperature shall be 180-220℃, and the curing time shall be 60-90min; S4. Surface treatment II: Apply the second coating glue After grinding and blowing, apply the second coating glue, the second coating glue is: 25-30 parts of graphite emulsion, 8-10 parts of flake graphite powder, 2-5 parts of silicon carbide powder, 10-12 parts of water; S5. Baking The baking temperature is 100-120°C and the baking time is 30-90 minutes; S6. Surface treatment III: Apply the third coating glue After grinding and purging, apply the third coating glue, which is: 10-12 parts of anhydrous ethanol, 1-3 parts of resin II, and 0.1-0.3 parts of graphite powder; S7, curing and sintering The curing temperature is 180-200°C, and the curing time is 30-60min; the sintering temperature is 1700°C-2200°C, and the sintering time is 4-6h.

3. The preparation method according to claim 2, characterized in that: In step S2, the resin I is a mixed solution of phenolic resin and furan resin, and the mass ratio thereof is 1:0.5-0.

8.

4. The preparation method according to claim 2 or 3, characterized in that: The carbon powder particle size is 30-50 μm.

5. The preparation method according to claim 2, characterized in that: In step S6, the resin II is a phenolic resin.

6. The preparation method according to claim 2 or 5, characterized in that: In step S6, the graphite powder has a particle size of 80-100 μm.

7. The preparation method according to claim 2, characterized in that: In step S1, the coarse sandpaper used for grinding is 400-600 mesh.

8. The preparation method according to claim 2, characterized in that: In step S4, the coarse sandpaper used for grinding is 120 mesh, 320 mesh and 600 mesh.

9. The preparation method according to claim 2, characterized in that: In step S6, the coarse sandpaper used for grinding is 800 grit.

Citation Information

Cited By

  • Preparation method of high-oxidation-resistance pyrolytic carbon coating of carbon fiber thermal insulation material

    CN120483772A

  • Preparation method of high-oxidation-resistance pyrolytic carbon coating of carbon fiber thermal insulation material

    CN120483772B